Electro-assisted selective uptake/release of phosphate using a graphene oxide/MgMn-layered double hydroxide composite. Issue 8 (4th February 2019) - Lai, Yi-Ting; Liu, Wei-Ting; Chen, Lih-Juann; Chang, Min-Chao; Lee, Chi-Young; Tai, Nyan-Hwa
Abstract : This study demonstrates a continuously tunable ultra-efficient phosphate uptake-release technique with electro-assistance using the proposed GO/MgMn-LDH-300 composites electrode. Abstract : Phosphorus is a unique, limited, and a critical element in agriculture and industrial applications. However, in the absence of proper control, wastewater from industries may contain excessive phosphate, which causes eutrophication of lakes and rivers. Current research on the uptake and release of phosphate from wastewater is time-consuming and may produce a harmful effect on the environment. Herein, we developed an ultra-efficient process for the selective uptake and release of phosphate in wastewater based on graphene oxide (GO)/magnesium manganese-layered double hydroxide (LDH) composites calcined at 300 °C (GO/MgMn-LDH-300). In the proposed continuous electrosorption-desorption system, the adsorbed phosphate can be quickly released by controlling the applied voltage. The intercalated GO within the layered structure increases the surface area and generates more mesopores for phosphate adsorption. In addition, the abundant oxygen-containing functional groups on GO interact with metal ions, enhance Mn oxidation, and thereby produce more active sites for phosphate adsorption. The tunable applied potential difference controls the electrostatic interactions between the LDH composites and phosphate; the LDH composites show ultrahigh efficiency, excellent recyclability, and selective phosphate removal, and the phosphate adsorption and desorption rates of 0.79 and 3.56 mg P g −1 min −1, respectively, have been achieved. Via incorporating a single-voltage control process, the GO/MgMn-LDH-300 composite electrodes performed excellently in phosphate removal from wastewater and exhibited an outstanding desorption capacity; this showed potential of this process for commercial wastewater treatment.